HUBUNGAN STRUKTUR KOMUNITAS PLANKTON DAN KUALITAS PERAIRAN MUARA SUNGAI BEROK BANGKA TENGAH - Dly, Nurliana Isroq; Utami, Eva; Pamungkas, Aditya (Universitas Mataram, 2025)
Plankton are the smallest biota that drift and inhabit marine and fresh waters. Plankton have a variety of responses and are susceptible to changes in water quality. The purpose of this research is to find out and analyze the structure of the plankton community and also the quality of the waters and their relationship using spearman correlation analysis. The time and place of the research was carried out of October 2022 in the waters of the Berok Estuary, Central Bangka, as many as 6 station points using the plankton net tool with the vertical method. Plankton samples were identified under a binocular microscope with three repetitions. The results showed that 67 species from 39 genus. Lowest plankton abundance at station 1, namely 82 cells/l and the highest at stations 5 and 6, namely 1,310 cells/l and 1,327 cells/l. The results of the analysis of the lowest plankton diversity index were at station 1, namely 1.945 and the highest at station 5, namely 3.265. The lowest uniformity index at station 1 is 0.620 and the highest at station 2 is 0.877. The lowest dominance index at station 5 is 0.055 and the highest at station 1 is 0.183. several water parameters have been tested according to quality standards, except brightness, nitrate and orthophosphate, will the appropriate parameters have been optimal for marine biota. The relationship of water quality including orthophosphate and current velocity a significant relationship to the plankton community structure in the waters of the Berok Estuary, Central Bangka